Dielectric properties of lead magnesium niobate-lead titanate ceramics prepared by mixed-oxide method - Rattikorn Yimnirun (2018)
In this study, the (1-x)Pb(Mg1/3Nb2/3)O3-xPbTiO3(when x=0.1, 0.3 and 0.5) ceramics were prepared from PMN and PT powders by a mixed-oxide method. The dielectric properties of the ceramics were measured as functions of both temperature (-150400°C) and frequency (100 Hz1 MHz). The results indicated that the dielectric properties of pseudo-cubic phase 0.9PMN-0.1PT and tetragonal phase 0.5PMN-0.5PT ceramics followed that of relaxor and normal ferroelectric behaviors, respectively, while the dielectric behaviors of a near MPB phase 0.7PMN-0.3PT ceramic showed a mixture of normal and relaxor ferroelectric behaviors. In addition, the Curie temperature (TC) increased with increasing PT contents, while the diffusivity decreased. This confirmed a gradual transition from a relaxor ferroelectric behavior in 0.9PMN-0.1PT to a normal ferroelectric behavior in 0.5PMN-0.5PT. The difference in dielectric behaviors was attributed to the structural symmetry of the ceramics. © 2009 World Scientific Publishing Company.